Exploring dryland cereals and legumes for addressing food security: ATLAS DCL CGIAR, Research Program on Dryland Cereals and Legumes Agri-Food Systems - Castaño, Silvia Elena; Hyman, Glenn G.; Rivera, Ovidio; Espinosa, Herlin (2016)
Population growth and climate change threatens the world’s capacity to produce food into the future. Dryland cereal and legume (DCL) crops are part of any global solution to food security challenges. But these crops are often overlooked and under researched when compared to the main staples such as rice, wheat and maize. What are the priority regions for research on dryland cereals and legumes? This study determined the priority regions for research on these crops. The DCL crops are chickpea, common bean, cowpea, faba bean, groundnut, lentil, pigeon pea, soybean, barley, pearl millet, small millet and sorghum.